2017
DOI: 10.1182/blood-2016-10-744060
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl sulfate induces platelet hyperactivity and contributes to chronic kidney disease–associated thrombosis in mice

Abstract: Key Points• Uremic solute IS increases platelet activity via activation of ROS/p38MAPK signaling.• Klotho counteracts ISinduced thrombosis by restraining platelet hyperactivity.Thrombosis is a common complication of chronic kidney disease (CKD), but the causes and mechanisms of CKD-associated thrombosis are not well clarified. Here, we show that platelet activity is remarkably enhanced in CKD mice, with increase of serum indoxyl sulfate (IS), a typical uremic toxin, which cannot be effectively cleared by routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 56 publications
(61 reference statements)
7
126
0
2
Order By: Relevance
“…Because thrombocytes are a major source of S1P, our finding may be related to thrombocytes activation in ESRD . This was also recently confirmed in a murine CKD model, where thrombocyte activity was remarkably enhanced with increase in serum indoxyl sulphate, a typical uremic toxin …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Because thrombocytes are a major source of S1P, our finding may be related to thrombocytes activation in ESRD . This was also recently confirmed in a murine CKD model, where thrombocyte activity was remarkably enhanced with increase in serum indoxyl sulphate, a typical uremic toxin …”
Section: Discussionsupporting
confidence: 77%
“…27 This was also recently confirmed in a murine CKD model, where thrombocyte activity was remarkably enhanced with increase in serum indoxyl sulphate, a typical uremic toxin. 28 Although higher plasma concentrations of S1P contribute to the significantly higher levels of the lipid associated with HDL, reduced albumin concentrations in the uremic milieu are also likely to contribute 29 . Whilst plasma S1P is principally associated with HDL, also albumin serves as a transport vector.…”
Section: Pvaluementioning
confidence: 99%
“…Although vessel wall factors and platelets in IS-mediated thrombosis are being examined (11, 18, 46), the roles of other metabolites (termed “thrombolome”) (3, 11), microvesicles, etc. remain to be probed to fully characterize the hyperthrombotic uremic milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that abnormal platelet function may be a major contributor to the imbalance. Similarly, a recent study observed markedly enhanced platelet activity in CKD mice, which could be attenuated by inhibiting MAPK signaling via klotho administration [27]. Regarding hub genes, FN1 and ACTA2 are well documented key regulators of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%